Study of electromagnetic enhancement for surface enhanced Raman spectroscopy of SiC graphene - Wee, Andrew T. S. (2013)
The electromagnetic enhancement for surface enhanced Raman spectroscopy (SERS) of graphene is studied by inserting a layer of Al2O3 between epitaxial graphene and Au nanoparticles. Different excitation lasers are utilized to study the relationship between laser wavelength and SERS. The theoretical calculation shows that the extinction spectrum of Au nanoparticles is modulated by the presence of graphene. The experimental results of the relationship between the excitation laser wavelength and the enhancement factor fit well with the calculated results. An exponential relationship is observed between the enhancement factor and the thickness of the spacer layer.